Matlamat Pembangunan Mampan (SDGS) dalam kerangka Malaysia Madani dan prinsip maqasid - Wan Fariza Alyati Wan Zakaria,; Ahmad Sunawari Long,; Zul`azmi Yaakob, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The human civilization in the modern era witnesses a significant humanitarian and environmental crisis that extends globally, resulting from the rapid development and economic growth. The ongoing debate in finding solutions to these global issues has led to several programs that becoming crucial agendas at the United Nations (UN) level, such as the Millennium Development Goals (MDGs) and more recently, the Sustainable Development Goals (SDGs). As a modern and progressive Islamic nation, Malaysia, through the Madani Framework, has endeavored to adapt the SDGs according to the needs and appropriateness of the country's values and norms in the context of a multiethnic and multireligious society. At the same time, Malaysia also strives to uphold universal and dynamic Islamic principles such as the maqasid shariah in implementing a sustainable and lasting development framework. This article discusses how the symbiosis of the maqasid principles, the Madani Framework, and the SDGs can be conceptually integrated to guide and propel the country towards creating civilizational value and progress for all of humanity.